Decision Support Systems Assessment of the best village in Perbaungan sub-district with the Simple Additive Weighting (SAW) Method: Decision Support Systems Assessment of the best village in Perbaungan sub-district with the Simple Additive Weighting (SAW) Method - Sri Devi; Hengki Tamando Sihotang (Institute of Computer Science (IOCS), 2019)
Information technology is a technology used to process data, including processing, obtaining, compiling storing, manipulating to produce quality information, which is relevant information that is accurate and timely in decision making. In the village assessment is an effort to encourage community efforts based on their own determination and strength as well as researching and assessing the success of community efforts in rural development such as improving the quality of economic, political, social, and cultural life as well as security and order. This research examines how to design an application and build a decision support system to facilitate the process of assessing the best villages. Using the Simple Additive Weighting (SAW) method, assess the best village to be more targeted. The SAW method certainly uses a more accurate assessment because it is based on the value of criteria and weight of predetermined preferences. This research produces a system that can display recommendations for the best village assessment with the results of the criteria that have been determined by the needs of the system.